Experimental Behaviour of Reinforced Concrete Corbels Strengthened with Carbon Fibre Reinforced Polymer Strips - Mohamad-Ali, Anis A.; Attiya, Muhammad Abed (Basrah Journal for Engineering Sciences, 2012)
This research is devoted to investigate the effect of Carbon Fibre Reinforced Polymer (CFRP) strips on the behaviour and load carrying capacity of strengthened and repaired reinforced concrete corbels. Experimental investigation were carried. The experimental program variables include location, direction, amount of CFRP strips and effect of shear span to effective depth (a/d) ratio on the behaviour of strengthened corbels. All corbels had the same dimensions and flexural reinforcement and they were without horizontal shear steel reinforcement. The experimental results obtained from the adopted strengthening and repairing CFRP techniques showed a significant improvement in the behaviour and carrying capacity of the tested corbels. An increase of about (44.5 - 60) % in the ultimate load has been obtained for specimens strengthening by inclined technique compared to the ultimate load of control corbel and (14.7 - 31.2)% for specimens strengthening horizontal technique. For corbels repaired with CFRP strips, an increase of (56%) with respect to the ultimate load of control corbel is achieved. Also the strengthened corbels show stiffer load deflection response than corresponding control corbels (unstrengthened corbels).